A rare variant of inferior vena cava anomalies: Double IVC with retrohepatic interruption and azygos continuation of both right and left IVCs - Khadija ElAitari; Najlae Lrhorfi; yahya Sqalli Houssaini; Kaoutar Maslouhi; Nazik Allali; Latifa Chat (Radiology Case Reports, 2025)
Congenital anomalies of the inferior vena cava (IVC) result from complex embryological development and can include rare variations such as duplication of the IVC and interruption of the retro hepatic segment with azygos continuation. We present a case of a double IVC associated with agenesis of the retro hepatic segment and azygos continuation. Although these anomalies are generally asymptomatic, they can predispose to the occurrence of deep vein thrombosis. Modern imaging, particularly computed tomography (CT), plays a crucial role in their detection and characterization. A thorough understanding of these variations is essential for adapting clinical management and avoiding complications during surgical interventions or endovascular procedures.